Assessment of GH reserve before and after successful treatment of adult patients with Cushing's syndrome. - Tzanela, M; Karavitaki, N; Stylianidou, C; Tsagarakis, S; Thalassinos, N (2004)
OBJECTIVE: Several studies have demonstrated impaired GH secretion in patients with active Cushing's syndrome (CS). It has been suggested that persistence of GH deficiency, despite treatment of cortisol excess, may delay the recovery of these patients and therefore temporary treatment with GH may have some benefit. However, the time course of restoration of GH secretion after successful treatment of CS has only been investigated in a limited number of mostly paediatric reports. The aim of the present study was the evaluation of GH reserve in adult patients with CS before and after correction of cortisol excess. DESIGN AND PATIENTS: Sixteen patients (12 females, four males) with CS aged 44.7 +/- 5.05 years were recruited. These included seven patients with Cushing's disease, four patients with ectopic ACTH secretion and five patients with adrenal adenoma. All patients were evaluated before any therapeutic intervention. Twelve patients were successfully treated following appropriate surgery and these were further studied. The combined pyridostigmine/GHRH test was used to assess GH reserve in these patients. In a proportion of cases an insulin tolerance test (ITT) was also used. RESULTS: Before any therapeutic intervention, an impaired GH response to PD/GHRH was noted in all patients. Restoration of GH response at 6 months was observed in six patients (50%); at 12 months in two; at 18 months in one patient. Two of the patients with no restoration of GH response at 12 months did not accept further investigation. Only one patient did not achieve an adequate GH response even when tested 30 months following cure of CS. Restoration of GH reserve was more commonly observed in those patients in whom there was recovery of the HPA axis. There was a good correlation between peak GH levels to PD + GHRH and ITT. No statistically significant difference was revealed in IGF-I levels between pre- and post-treatment evaluation. CONCLUSIONS: Adult patients with active Cushing's syndrome demonstrate a profound suppression of stimulated GH secretion. In the majority of these patients the disruption of GH secretion is normalized within a year after successful treatment of endogenous cortisol excess.